The Belcher Islands / from plans and sketches of Robert J. Flaherty, F.R.G.S. - Flaherty, Robert Joseph, 1884-1951 (New York : American Geographical Society of New York, 1918)
Relief indicated by spot height. Indicates course of ship "Laddie," 1914-1915. From: The Geographical Review, vol. V, No. 6, 1918, pl. IV. Color 1:1:500,000